Ancaman Cybercrime dan Peran Cybersecurity pada E-commerce: Systematic Literature Review - Muhammad Irfan; Mairisa Elvia; Shaquila Dania (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
This study aims to determine the cybercrime challenges faced by e-commerce as well as anticipatory actions in the form of cybersecurity to overcome these challenges. This study used a systematic literature review (SLR) method. The results show that the handling of cyber crimes in e-commerce must be carried out collectively by customers e-commerce companies, and law enforcement. Consumers should always be vigilant and ensure that they do not provide personal information to people or organizations they cannot trust. The limitations of this study are limited to providing an overview and elaboration of the research results from each of the selected articles, but does not provide further analysis regarding the interrelationships between the articles discussed. Recommendations for further research can add to the scope of the article under study. Keywords: Cybercrime, Cybersecurity, E-commerce